Hydrological assessment for mini hydropower potential at Sungai Pahang @ Temerloh - Sidek L.M.; Zaki A.Z.A.; Mustaffa Z.; Ibrahim M.I.H.; Muda Z.C.; Thiruchelvam S.; Basri H. (Institute of Physics Publishing, 2023)
Sg Pahang at Temerloh was considered for assessment of hydropower potential using hydrological analysis method and hydrological model. The available data related to topography, soil, land use, weather and discharge pertaining to the study catchment were used to characterize the catchment. The characterization was required for water resources hence hydropower assessment. The hydrology of the study catchment was simulated through the model. This hydrological study is required due to the proposed mini hydroelectric power plant at Pulau Temerloh. It is essential to evaluate the existing river flow characteristic and to model the environmental flow assessment of the river. Two rainfalll stations, JPS Temerloh and Pintu Kawalan Paya Kertam Station are selected to develop the Rainfall Intensity Duration frequency (RIDF) Curve to determine the rainfall intensity of the area. Daily river flow were recorded at Sg Pahang at Temerloh and Sg Pahang at Lubok Paku were used to develop the Flow Duration Curve (FDC) to study the characteristic of Sungai Pahang flow. The 7 days low flow with 10 years return period (7Q10 low flow) was obtained using both Gumbel Method and Log Pearson Type III Method. The results from FDC shows that 50% percentage of time the Sg Pahang @ Temerloh is exceeded over a historical period is 400 m 3/s and 50% percentage of time the Sg Pahang @ Lubok Paku is exceeded over a historical period is 650 m3/s. The required environmental flow are set to be 7Q10 low flow which is 64.215 m3/s for Sg Pahang at Temerloh and 79.24 m3/s for Sg Pahang at Lubok Paku. The results show the water resources are abundant and hence boost the mini hydropower potentiality at Sg Pahang. Published under licence by IOP Publishing Ltd.